2017
DOI: 10.1103/physrevb.96.161112
|View full text |Cite
|
Sign up to set email alerts
|

Topological surface electronic states in candidate nodal-line semimetal CaAgAs

Abstract: We investigate systematically the bulk and surface electronic structure of the candidate nodal-line semimetal CaAgAs by angle-resolved photoemission spectroscopy and density functional calculations. We observed a metallic, linear, non-k z -dispersive surface band that coincides with the high-binding-energy part of the theoretical topological surface state, proving the topological nontriviality of the system. An overall downshift of the experimental Fermi level points to a rigid-band-like p doping of the sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…More importantly, we identify distinct surface states emanating from the bulk nodal lines, the surface signatures demonstrate the nontrivial topology of the nodal-line semimetal states in ZrB 2 .Compared with the previous nodal-line candidates CaAgAs, PbTaSe 2 , and the ZrSiS family[28][29][30][31][32][33] , ZrB 2 has the following advantages: (1) the whole band-crossing features forming the nodal lines are clearly resolved below the Fermi energy (E F ) in ZrB 2 , while the nodes of CaAgAs 28 , PbTaSe 2 29 ,…”
mentioning
confidence: 73%
“…More importantly, we identify distinct surface states emanating from the bulk nodal lines, the surface signatures demonstrate the nontrivial topology of the nodal-line semimetal states in ZrB 2 .Compared with the previous nodal-line candidates CaAgAs, PbTaSe 2 , and the ZrSiS family[28][29][30][31][32][33] , ZrB 2 has the following advantages: (1) the whole band-crossing features forming the nodal lines are clearly resolved below the Fermi energy (E F ) in ZrB 2 , while the nodes of CaAgAs 28 , PbTaSe 2 29 ,…”
mentioning
confidence: 73%
“…In the search for nodal-line semimetals, several systems have been theoretically proposed since 2011 2,3 . However, only a few candidates including PbTaSe 2 13,14 , ZrSiX (X = S, Se, Te) 15,16 , CaAgX (X = P, As) 17,18 , and MB 2 (M = Ti, Zr) 19 have been verified experimentally. More recently, the CaP 3 family of materials (MAs 3 , for M = Ca, Ba, and SrX 3 for X = P, As) was proposed as another potential host of TNLSMs 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to strong spin-orbit interaction rare earth based pnictide LaBi is a TI which is verified experimentally [20]. with the topological surface state in CaAgAs [22]. On the other hand, Takane et al concluded from bulk sensitive soft X-ray photoemission that CaAgAs belongs to the family of nodal line semimetals [23].…”
mentioning
confidence: 99%